2022
DOI: 10.3390/ijerph19126982
|View full text |Cite
|
Sign up to set email alerts
|

Does Digital Inclusive Finance Effectively Promote Agricultural Green Development?—A Case Study of China

Abstract: Agricultural green development is increasingly being discussed in sustainable development. This paper constructs agricultural green development from four dimensions: resource savings, environmental protection, ecological conservation, and quality industrialization. We apply the entropy-weighted Technique for Order Preference by Similarity to an Ideal Solution (TOPSIS) method to measure agricultural green development and employ a panel dataset of provinces in China from 2011–2019. Then, the dynamic spatial Durb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 44 publications
2
30
0
Order By: Relevance
“…The green development level integrates the sustainability of the three subsystems of economy, society, and ecological environment. Based on the above analysis and existing studies [ 7 , 8 , 9 , 23 , 37 , 38 , 39 , 40 , 41 , 42 , 43 ], we constructed an evaluation index system of the green development level of cities in the Yangtze River Economic Belt based on data availability, with the green development level as the target layer and growth quality, industrial development, resource utilization, environmental carrying capacity, environmental governance, and green life as the guideline layer, as shown in Table 1 .…”
Section: Evaluation Index System For Green Development Performancementioning
confidence: 99%
See 1 more Smart Citation
“…The green development level integrates the sustainability of the three subsystems of economy, society, and ecological environment. Based on the above analysis and existing studies [ 7 , 8 , 9 , 23 , 37 , 38 , 39 , 40 , 41 , 42 , 43 ], we constructed an evaluation index system of the green development level of cities in the Yangtze River Economic Belt based on data availability, with the green development level as the target layer and growth quality, industrial development, resource utilization, environmental carrying capacity, environmental governance, and green life as the guideline layer, as shown in Table 1 .…”
Section: Evaluation Index System For Green Development Performancementioning
confidence: 99%
“…Environmental governance, as one of the core elements of the green development of the Yangtze River Economic Belt, is an important tool to guarantee green development [ 7 , 40 , 42 ].…”
Section: Evaluation Index System For Green Development Performancementioning
confidence: 99%
“…The coverage breadth mainly includes three indicators: the number of Alipay accounts, the proportion of Alipay account-bound users, and the number of Alipay account-bound cards, which reflect numbers Financial coverage; the depth of use covers payment, credit, insurance, investment, and monetary funds and other services, reflecting the increase in the variety and availability of digital financial instruments; the digitalization degree includes mobile, affordability and facilitation, which can reflect the degree of integration and inclusiveness of digital finance and digital technology. The index has been widely applied to the field of China’s DIF [ 9 , 26 ], and has considerable representativeness and reliability. This paper uses these three sub-indicators as explanatory variables to further explore the impact of different dimensions of digital finance on ACEP.…”
Section: Methodsmentioning
confidence: 99%
“…Emerging digital inclusive finance (DIF) can overcome the challenges that traditional finance faces. It is a new financial service model to improve financial inclusion by using digitial technologies and the Internet [ 9 , 10 ]. In recent years, China’s world-leading DIF is reshaping the way of production and life.…”
Section: Introductionmentioning
confidence: 99%
“…Gao et al (2022) found that the development of digital inclusive finance was an important path to motivate agricultural technology innovation and industrial structure optimization in China, which helped drive Chinese agriculture to improve agricultural total factor productivity and achieve high-quality development [ 27 ]. Based on a panel dataset of Chinese provinces from 2011 to 2019, Guo et al (2022) constructed agricultural green development indicators from four dimensions of resource savings, environmental protection, ecological conservation, and quality industrialization and confirmed that digital inclusive finance have effectively promoted the green development of Chinese agriculture [ 28 ]. Zhong et al (2022) found that the digital financial inclusion in China had a promoting effect on China’s agricultural technological progress, which in turn inhibited the intensity of agricultural carbon emissions in China [ 29 ].…”
Section: Literature Reviewmentioning
confidence: 99%